VD_FINDINFO Jug / 2023 / 508 vom 1. Januar 2021 - VD Tribunal cantonal (2021)
DROIT AU SALAIRE, SALAIRE, DROIT D'ÊTRE ENTENDU, LÉGALITÉ, PROPORTIONNALITÉ, NE BIS IN IDEM, AUGMENTATIONEN GÉNÉRAL | 29 al. 2 Cst., 26 LPers-VD, 43 RLPers-VD